Hubungan Antara Efikasi Diri dengan Kematangan Emosi pada Siswa SMP yang Mengikuti Ekstrakurikuler Pramuka - Felix Chandra; Antonius Ian Bayu Setiawan (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the level of self-efficacy and emotional maturity and the relationship between the two in junior high school students who participate in scouting extracurricular activities. This study uses a quantitative correlational method, involving 95 students from St. Aloysius Turi Junior High School as a sample.